Elementary School Student Creativity in Solving Geometry Contextual Problems based on Adversity Quotient - Dyen Erni Lakapu; Neni Mariana (IndoMath: Indonesia Mathematics Education, 2020)
Creativity is an ability that is needed in solving a problem. A person's creativity in solving problems can be assessed using three components namely fluency, flexibility, and novelty. Someone in solving problems can be influenced by the adversity quotient they have. There are three categories of adversity quotient namely quitter, camper, and climber. This type of research is a qualitative research method descriptive. This study aims to describe the creativity of elementary school students in solving contextual geometry problems based on adversity quotient. The subjects in this study were three people consisting of quitter subjects, camper subjects, and climber subjects. Data is collected through adversity Response Profile (ARP) tests, Problem Solving Tests (TPM) and interviews. The results showed that the creativity of subjects with the quitter category in solving contextual geometry problems was not able to achieve fluency, flexibility, and novelty. The creativity of subjects with camper categories in solving contextual geometry problems only achieves fluency and flexibility. Whereas the creativity of subjects with climber types in solving contextual geometry problems is able to achieve fluency, flexibility, and novelty.